The Energy Efficient Techniques for Wireless Sensor Networks: A Review - Neelam; Khosla, Dishant (International Journal of Computer Sciences and Engineering, 2016)
The wireless sensor networks are the type of network in which sensor nodes sense the environmental conditions and pass the sensed information to base station. The sensor network is deployed on the far places like forests, deserts etc. The size of the sensor node is very small due to which it is very difficult to recharge or replace battery of these sensor nodes. The various techniques has been proposed in the previous times, to reduce energy consumption of the network. Among various proposed techniques, clustering is the efficient technique to reduce energy consumption of the sensor networks. The clustering is of two types dynamic and static and in this article techniques of both type of clustering is reviewed and compared in terms of various parameters.